2011
DOI: 10.1002/14651858.cd006383.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin detemir versus insulin glargine for type 2 diabetes mellitus

Abstract: Our analyses suggest that there is no clinically relevant difference in efficacy or safety between insulin detemir and insulin glargine for targeting hyperglycaemia. However, to achieve the same glycaemic control insulin detemir was often injected twice-daily in a higher dose but with less weight gain, while insulin glargine was injected once-daily, with somewhat fewer injection site reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 34 publications
4
110
3
3
Order By: Relevance
“…Hypoglycaemia is a potent stimulus for energy intake and a plausible model for the weight‐sparing effects of insulin detemir, given the documented lower risk of hypoglycaemia with insulin detemir compared with human insulin 9; however, data from clinical trials comparing insulin detemir and insulin glargine show similar reductions in hypoglycaemia but show weight‐sparing only with insulin detemir 10. Moreover, Davies et al.…”
Section: Food Intake Modelmentioning
confidence: 99%
“…Hypoglycaemia is a potent stimulus for energy intake and a plausible model for the weight‐sparing effects of insulin detemir, given the documented lower risk of hypoglycaemia with insulin detemir compared with human insulin 9; however, data from clinical trials comparing insulin detemir and insulin glargine show similar reductions in hypoglycaemia but show weight‐sparing only with insulin detemir 10. Moreover, Davies et al.…”
Section: Food Intake Modelmentioning
confidence: 99%
“…Heise et al compared the pharmacokinetic profile of a single dose of s.c. NPH insulin, insulin glargine, and insulin detemir by the glucose-infusion rate (GIR) during a euglycemic clamp technique in patients with T1D. The authors reported the GIR of the first 12 h to be 27 and 44% higher for insulin detemir and NPH insulin, respectively, than that observed following insulin glargine (21,22). Circulating IGFBP1 originates from the liver and its synthesis is primarily regulated by insulin, whereas glucose as also shown in this study plays a minor role (23).…”
Section: Discussionmentioning
confidence: 99%
“…Estudios que comparan las dos primeras no han demostrado diferencias significativas entre ellas 45 . Ensayos clí-nicos en pacientes diabéticos con función renal normal sugieren que degludec tiene una efectividad similar a glargina en la disminución de la glucemia, con menor riesgo de producir hipoglucemia, lo que lo convierte en un medicamento muy útil para el control diabético 46-49 .…”
Section: Segundo Nivel De Atenciónunclassified